Transposons and the PIWI pathway: genome defense in gametes and embryos. Issue 4 (October 2018) - Russell, Stewart J; LaMarre, Jonathan
Abstract : Hiding in plain sight within the genome of virtually every eukaryotic organism are large numbers of sequences known as transposable elements (TEs). These sequences often comprise 50% or more of the DNA in many mammals and are transcriptionally constrained by DNA methylation and repressive chromatin marks. Individual TEs, when relieved of these epigenetic constraints, can readily move from one genomic location to another, either directly or through RNA intermediates. Demethylation and removal of repressive histone marks during epigenetic reprogramming stages of gametogenesis and embryogenesis render the genome particularly susceptible to increased TE mobilization, which has significant implications for the fidelity of genome replication and subsequent viability of the progeny. Importantly, however, TEs have functionally integrated themselves into developmental events to the extent that complete suppression precludes normal gamete and embryo development. Consequently, multiple mechanisms have evolved to limit the extent of TE expression and mobilization during reprogramming without completely suppressing it. One of the most important TE repression mechanisms is the PIWI/piRNA pathway, in which 25–32 nucleotide RNA molecules known as piRNAs associate with Argonaute proteins from the PIWI clade to form piRISC complexes. These complexes target and silence TEs post-transcriptionally and through the induction of epigenetic changes at the loci from which they are expressed. This review will briefly discuss the intricate molecular détente between TE expression and its suppression by the PIWI pathway, with particular emphasis on mammalian species including human, bovine and murine.